RECRUITMENT OF MINORITY ADOLESCENTS AND YOUNG ADULTS INTO RANDOMISED CLINICAL TRIALS: TESTING THE DESIGN OF THE TECHNOLOGY ENHANCED COMMUNITY HEALTH NURSING (TECH-N) PELVIC INFLAMMATORY DISEASE TRIAL. (2016) - Trent, Maria; Anders, Jennifer; Chung, Shang-en; Huettner, Steven; Gaydos, Charlotte; Rothman, Richard; Frick, Kevin D.; Butz, Arlene
No abstract available